Analysis of Nahwu Learning Achievement: A Comparative Study of Regular and Intensive Programs at The Ar-Ridho Modern Islamic Boarding School - Maulana Farhan Gianmoko; Ana Taqwa Wati (Jendela Pendidikan : Jurnal Ilmiah Keguruan dan Ilmu Pendidikan, 2026)
Islamic boarding schools apply different learning systems in teaching Nahwu, namely the Regular Program (six years) with a distributed learning pattern and the Intensive Program (four years) with a massed or condensed learning pattern. This difference in instructional design raises an important question: which program produces better academic achievement in Nahwu? This research aims to determine whether there are differences in academic achievement in Nahwu between students in the Regular Program (six years) and the Intensive Program (four years) at the Ar-Ridho Sentul Modern Islamic Boarding School. This study uses a comparative quantitative approach with a sample of 356 students. Data were obtained from official grade documentation and analyzed using the Mann-Whitney U nonparametric test because the data distribution was not normal. The results of the analysis showed a statistically significant difference (p = 0.001 < 0.05) between the two groups. The Regular group had a Mean Rank of 183.64, while the Intensive group had only 120.55. These findings indicate that distributed practice in the Regular Program is more effective in strengthening long-term memory retention than the intensive learning pattern in the Intensive Program, which can increase cognitive load. The research recommends evaluating and adjusting learning strategies so that Islamic boarding school administrators can optimize student academic achievement.